Characterization of the USDA Cucurbita pepo, C. moschata, and C. maxima germplasm collections - Hernandez, Christopher O.; Labate, Joanne; Reitsma, Kathleen; Fabrizio, Jack; Bao, Kan; Fei, Zhangjun; Grumet, Rebecca; Mazourek, Michael (Frontiers in Plant Science, 2023)
The Cucurbita genus is home to a number of economically and culturally important species. We present the analysis of genotype data generated through genotyping-by-sequencing of the USDA germplasm collections of Cucurbita pepo, C. moschata, and C. maxima. These collections include a mixture of wild, landrace, and cultivated specimens from all over the world. Roughly 1,500 - 32,000 high-quality single nucleotide polymorphisms (SNPs) were called in each of the collections, which ranged in size from 314 to 829 accessions. Genomic analyses were conducted to characterize the diversity in each of the species. Analysis revealed extensive structure corresponding to a combination of geographical origin and morphotype/market class. Genome-wide associate studies (GWAS) were conducted using both historical and contemporary data. Signals were observed for several traits, but the strongest was for the bush (Bu) gene in C. pepo. Analysis of genomic heritability, together with population structure and GWAS results, was used to demonstrate a close alignment of seed size in C. pepo, maturity in C. moschata, and plant habit in C. maxima with genetic subgroups. These data represent a large, valuable collection of sequenced Cucurbita that can be used to direct the maintenance of genetic diversity, for developing breeding resources, and to help prioritize whole-genome re-sequencing.